Invasive species' leaf traits and dissimilarity from natives shape their impact on nitrogen cycling: a meta‐analysis. Issue 1 (8th August 2016) - Lee, Marissa R.; Bernhardt, Emily S.; van Bodegom, Peter M.; Cornelissen, J. Hans C.; Kattge, Jens; Laughlin, Daniel C.; Niinemets, Ülo; Peñuelas, Josep; Reich, Peter B.; Yguel, Benjamin; Wright, Justin P.
Summary: Many exotic species have little apparent impact on ecosystem processes, whereas others have dramatic consequences for human and ecosystem health. There is growing evidence that invasions foster eutrophication. We need to identify species that are harmful and systems that are vulnerable to anticipate these consequences. Species' traits may provide the necessary insights. We conducted a global meta‐analysis to determine whether plant leaf and litter functional traits, and particularly leaf and litter nitrogen (N) content and carbon: nitrogen (C : N) ratio, explain variation in invasive species' impacts on soil N cycling. Dissimilarity in leaf and litter traits among invaded and noninvaded plant communities control the magnitude and direction of invasion impacts on N cycling. Invasions that caused the greatest increases in soil inorganic N and mineralization rates had a much greater litter N content and lower litter C : N in the invaded than the reference community. Trait dissimilarities were better predictors than the trait values of invasive species alone. Quantifying baseline community tissue traits, in addition to those of the invasive species, is critical to understanding the impacts of invasion on soil N cycling.